Where is the Voice of Canada's Voluntary Sector - Elson, Peter R. (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2008)
Voluntary organizations in general and charities in particular have consistently contendedthat government regulations and fear of contractual reprisals constrain their capacity toadvocate for progressive social policies. This mticle focuses on the regulatory and institutionalside of this equation and contends that advocacy constraints exhibited by charitiesmay be less attributable to limits externally imposed by the federal government thanthey are to limitations on the institutional structure by which charities choose to organize.The Can& Revenue Agency was chosen because it has the widest influence on what isconsidered permissible political activities by charities across Canada. This study exploredchanges across three iterations of Canada Revenue Agency regulations concerning permissiblepolitical activities and resource allocation limits by registered charities. Between therelease of Information Circular 78-3 in 1978, which was viewed by the voluntary sectoras punitive and restrictive, and Political Activities CPS-022 in 2003, permissible politicalactivities have been clarified and expanded. This study goes on to analyqe the institutionalstructure which characterized the voluntary sector and government when substantivepolicy dialogue developments took place across this twenty-five year period. This studyconcludes that the non-formal institutional structure characteristic of voluntary sectorrepresentation and reporting has influenced both the lack of legislative change and thenature and impact of sectoral advocacy. The voluntary sector in Canada would be wellserved by increasing its institutional structure formality and charities should work togetherto take full advantage of the potential new advocacy capacity available through PoliticalActivities CPS-022.Les organismes be'ne'voles en ge'n&ral, et plus particuli2rement les organismes de bienfaisance,ont toujours pktendu que les r?glements gouvernementaux et la crainte de repre'saillescontractuelles limitent kur capacite' h militer pour des politiques sociales pogressistes.L'article, qui s'attarde h l'aspect rkglementaire et institutionnel de cette e'quation, avanceque les contraintes lie'es au militantisme pre'sente'es par les organismes de bienfaisancepoumaient Ctre &vantage attribuables aux limites de la structure institutionnelle sousIaquelle ces organismes choisissent d'exercer leurs activite's qu'aux limites impose'es par legouvernement fe'de'ral. L'auteur a choisi de se pencher sur llAgence du revenu du Canadaparce qu'elle ewrce l'influence la plus importante sur la &finition des activitb politiquesadmissibles des organismes caritatifs au Canada. L'e'tude a examine' les modificationsapporte'es lors de trois p~ksentations successives des r2glements de I'Agence du revenudu Canada relativement aux actiuite's politiques admissibks et aux limites d'allocationde ressources des urganismes de bienfaisance. Entre le lancement de la Circulaire#information 78-3 en 1978, juge'e punitive et restrictive par le secteur be'ne'vole etcommunautaire, et celui de l'e'nonce' de politique Activitks politiques CPS-022 en2003, les actiuit6s politiques admissibles ont it6 clanfie'es et e'tendues. L'e'tude proposeensuite une analyse de h structure institutionnelle qui a caructe'rise' la relation entre lesecteur be'ne'vole et le gouvernement lorsque &S de'veloppements importants du dialoguerelatif aux politiques sont survenus durant cette pkiode de 25 ans. L'auteur conclut quela structure institutionnelle informelle prope h la repre'sentation et h la production de rapportsdu secteur be'nkvole a exerce' une influence tant sur le manque de changementsd!ordre le'gislatif que sur la nature et l'imnpuct du militantisme de ce secteur. Le secteurbe'ne'vole du Canada be'ne'ficierait d'une formalisation de sa structure institutionnelle, etles organismes caritatifs dewraient unir leurs efforts afin de profiter au maximum desnouvelles possibilite's de militantisme offertes par l'e'nonce' de politique Activitks politiquesCPS-022.